Differential Expression of CD43, CD81, and CD200 in Classic Versus Variant Hairy Cell Leukemia. Issue 4 (11th May 2019) - Salem, Dalia A.; Scott, Drake; McCoy, Catharine S.; Liewehr, David J.; Venzon, David J.; Arons, Evgeny; Kreitman, Robert J.; Stetler‐Stevenson, Maryalice; Yuan, Constance M.
Abstract : Background: Hairy cell leukemia (HCL) and hairy cell leukemia variant (HCLv) are rare diseases with overlapping clinicopathological features. Features distinguishing HCL from HCLv include expression of CD25, CD123, CD200, annexin‐A1, and the presence of BRAF V600E mutation. HCLv typically lacks these markers, but they may occur in a subgroup of HCL patients with an aggressive clinical course. We examined CD43, CD81, CD79b, and CD200 expression in HCL and HCLv. Methods: Multiparametric flow cytometry (FCM) was performed on blood from 59 HCL and 15 HCLv patients for protocol entry. Mean fluorescent intensity (MFI) of CD43, CD79b, CD81, and CD200 was determined (for CD200, n = 17 and 7, respectively). Results: Median MFI of HCL vs HCLv was 545 vs 272 for CD43, 602 vs 2, 450 for CD81, 4, 962 vs 1, 969 for CD79b, and 11, 652 vs 1, 405 for CD200, respectively. Analysis of the median differences, HCL minus HCLv (and their 95% confidence intervals and P ‐values) indicated that CD43 MFI (estimated median difference (95% CI): 212 [72–413; P = 0.0027) and CD200 MFI (9, 883 [3, 514–13, 434]; P < 0.0001) were higher in HCL than in HCLv, while CD81 MFI (−1, 858 [−2, 604 to −1, 365]; P < 0.0001) was lower in HCL than in HCLv. CD79b MFI HCL median was more than double that of HCLv, but the observed difference (1, 571 [−739 to 4, 417]) was consistent with the null hypothesis of no difference ( P = 0.13). Conclusions: CD200, CD43, and CD81 are likely differentially expressed between HCL and HCLv, reflecting their differing disease biology. Inclusion of these markers in FCM is potentially informative. © 2019 International Clinical Cytometry Society